Pemberdayaan Masyarakat melalui Digitalisasi UMKM, Pemanfaatan Limbah Rumah Tangga, serta Edukasi Penggunaan Gadget Bijak bagi Remaja - Muhammad Nabil; Yoga Eka Prasetya; Muhammad Zamrozi; Bagus Hari Sugiharto (Penerbit Goodwood, 2026)
Purpose: This training aims to increase knowledge of UMKM digitalization, household waste utilization, and wise gadget education in increasing community independence and welfare.Methodology: The training was held in Baujeng village, Pasuruan, in June 2025. This activity used training and counseling methods supported by tools and equipment such as projectors and laptop, with activity stages including presentation materials, activity simulations, question and answer session, and discussions.Results: Based on the training results, it can be concluded that the majority of the population is less aware of technological developments. This is evident in the lack of use of technology today, which could actually make work easier. Furthermore, teenagers are also less wise in their gadget use, as the majority use them for gaming and scrolling through social media.Conclusions: This training has proven effective in improving MSMEs' basic understanding of how to utilize technology to facilitate sales. It also raises awareness among young people about using gadgets more wisely.Limitations: A limitation of this study is that the sample only included participants from Baujeng Village; therefore, the results may not be representative of all MSMEs in Indonesia. Furthermore, the short duration of the training and the evaluation, which was based solely on a brief post-training questionnaire, make this study less comprehensive.Contribution: This training demonstrates significant potential to help business owners optimize their business development. Future recommendations include ongoing training, individual mentoring, and the development of online training modules.